PROFIL LITERASI ARTIFICIAL INTELLIGENCE (AI) GURU SMAN 1 MRANGGEN KABUPATEN DEMAK - Budi Minarti, Ipah; Nurwahyunani, Atip; Citraning Rachmawati, Rivanna (Jurnal Biogenerasi, 2025)
TPACK (Technological Pedagogical and Content Knowledge) is a basic skill for educators in today's modern era. Even TPACK is referred to as one of the factors that determines the success or failure of learning activities carried out, namely a teacher, so the quality of teachers can be an important factor in improving the quality of education. Teachers are required to have several competencies in the form of a set of mastery of abilities that must be present in teachers, especially in the use of technology, one of which is the application of AI (Artificial Intelligence). For teachers, the use of AI technology can help improve teaching skills, professional development, and provide support in learning assessment and management. This study uses a qualitative research method using a qualitative inductive analysis approach. Qualitative data is collected through activities to make notes of data and information that is heard and seen, then the data is analyzed. The results of the study show that the AI ​​digital literacy profile of teachers at SMAN 1 Mranggen can be concluded to be in the Very Good category (85%) with the following 3 indicators: 1) Ability to use digital media, namely 87% (Very Good); 2) Critical Understanding, namely 90% (Very Good); 3) Communication Skills, namely 76% (Good).